THE EFFECT OF BIOLOGICALLY ACTIVE SUBSTANCES ON THE PHOTOSYNTHETIC PROCESS IN SOYBEAN - Sobirova Mohinur Zokirjon qizi (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This study investigates the impact of biologically active substances (BAS) on the photosynthetic activity of soybean (Glycine max L.) plants under field conditions. Specifically, plant growth regulators, amino acid-based biostimulants, and natural extracts were applied during the vegetative and flowering stages. The treatments led to a significant increase in chlorophyll content, net photosynthetic rate, and stomatal conductivity compared to untreated controls. These effects resulted in enhanced plant growth and biomass accumulation. The findings suggest that biologically active substances play a critical role in optimizing photosynthetic efficiency, especially under environmental stress conditions, thereby contributing to improved crop productivity.